Pulse Scattering on Objects in the Inhomogeneous Conducting Medium - Varyaniza-Roshchupkina, L.A.; Kovalenko, V.O. (Радиофизика и радиоастрономия, 2002)
The objective of the work is to present the results of computer simulation of the problem of pulse scattering on cylinder objects buried in the inhomogeneous conducting medium. The finite difference time domain method (FD-TD) is used for solving the problem. The grid discretization in space and time is carried out taking into account the required stability of the realized method. The elementary absorbing boundary conditions (ABC), such as the perfect matched layer, Bayliss-Turkel annihilation operators and the Mur finite-difference scheme have been realized. Visualization of the results obtained has been carried out, and scattered field images have been constructed.